Co-administration of Coenzyme Q10 and HMG-CoA Reductase Inhibitor Attenuates Oxidative Stress, TGF-β, TNF-α, Nitrite Content and MPO Levels against Experimentally-induced Diabetic Nephropathy in Rats - Maheshwari, Rajesh A.; Sen, Ashim Kumar; Balaraman, Ramachandran; Shah, Nirmal V.; Shah, Umang H.; Solanki, Nilay; Sen, Dhanya B. (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: Diabetes is a major disease that causes a tremendous economic burden internationally. To tackle this horrible condition, good therapeutic intervention with nutraceutical is required. These include diabetic nephropathy, which ranges from chronic kidney disease to end-stage renal failure. Thus, this study used nutraceutical such coenzyme Q10 and HMG-CoA reductase inhibitor (rosuvastatin) to see how beneficial they are in treating diabetic nephropathy. Materials and Methods: The animal experiments were conducted to induce nephropathy by using streptozotocin-nicotinamide. Animals were divided into five groups such as control, diabetic control, coenzyme Q10, rosuvastatin and their combination. The renal function test was conducted by estimating uric acid, creatinine and urea. Antioxidant parameters were assessed by evaluating MDA, SOD, GSH and catalase activity in renal tissue. Levels of MPO, TGF-β, TNF-α and nitrite concentration were measured together with alterations in histopathology in the kidneys were observed in every treated animal. Results: Diabetic rats were studied for signs of nephropathy, and the results showed elevated levels of urea, creatinine, uric acid, MPO activity, TGF-β, TNF-α, nitrite and MDA as well as decreased levels of GSH, SOD and CAT activity. It was shown that when coenzyme Q10 and rosuvastatin were given combined, renal function tests improved far more quickly than when the two medications were given separately. Conclusion: This study found that combination therapy improved renal function and controlled free radical production, inflammatory mediators, and histological alterations that lead to kidney injury.
Keywords: Diabetic nephropathy; MPO activity; TNF-α; TGF-β; Coenzyme Q10